2020
DOI: 10.1002/iub.2347
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein protects against lipopolysaccharide‐induced sepsis and alleviates inflammatory responses in mice

Abstract: Sepsis results from a major systemic inflammatory response and can induce disorders in multiple organs. The present study evaluated the potential protective effects of oleuropein (OLE) against hyperinflammatory responses during lipopolysaccharide (LPS)‐induced sepsis in mice. Sixty male Balb/c mice were randomly categorized into five groups of 12 animals each: control, intraperitoneally injected with OLE (50 mg/kg), injected with LPS (10 mg/kg, intraperitoneal), and two groups administered OLE (25 and 50 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…injected with a single dose of LPS (10 mg/kg b.w.) dissolved in endotoxin-free saline (Alsharif et al, 2020); Group 4, 5, and 6 (PCA10-LPS, PCA20-LPS, and PCA30-LPS groups, respectively) mice were orally administered PCA at doses of 10 (low dose), 20 (average dose), and 30 (high dose) mg/kg b.w., respectively, for seven days followed by LPS injection as previously described.…”
Section: Experimental Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…injected with a single dose of LPS (10 mg/kg b.w.) dissolved in endotoxin-free saline (Alsharif et al, 2020); Group 4, 5, and 6 (PCA10-LPS, PCA20-LPS, and PCA30-LPS groups, respectively) mice were orally administered PCA at doses of 10 (low dose), 20 (average dose), and 30 (high dose) mg/kg b.w., respectively, for seven days followed by LPS injection as previously described.…”
Section: Experimental Modelmentioning
confidence: 99%
“…Sepsis is considered a life-threatening and serious illness syndrome that occurs due to dysregulation of the host response to infection (Alsharif et al, 2020). Epidemiological studies have shown that septic shock and multiple organ dysfunction syndromes are the main causes of death in half or more of the patients in intensive care unit (Mutlu & Budinger, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, single cytokine, or a combination of multiple cytokines, including G-CSF, GM-CSF, IFN-γ, IL-3, IL-7, and IL-15, were introduced into sepsis therapy, according to a disease-specific progression and patient immune responses [ 8 ]. Some immunosuppressive agents, such as bursopentin [ 9 ], curcumin [ 10 ], and oleuropein [ 11 ], provided protection against inflammatory injury in the LPS-induced sepsis models.…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is usually applied in animal model to induce systemic inflammation 46,47 and also applied in leukocytes or other cells to induce inflammatory reactions or cell damage 48,49 . However, LPS is seldom applied in neutrophils to examine transendothelial migration.…”
Section: Discussionmentioning
confidence: 99%